Two-dimensional topological crystalline insulator phase in quantum wells of trivial insulators. (27th June 2016) - Niu, Chengwang; Buhl, Patrick M; Bihlmayer, Gustav; Wortmann, Daniel; Blügel, Stefan; Mokrousov, Yuriy
Abstract: The realization of two-dimensional (2D) topological insulators (TIs) in HgTe/CdTe quantum wells (QWs) has generated an explosion of research on TIs and novel topologically nontrivial phases. Here we predict, based on first-principles calculations, that the newly discovered 2D topological crystalline insulators (TCIs) phase exists even in the QWs of trivial insulators, e.g. (Sn/Pb)Te and Na(Cl/Br), with mirror Chern number n M = − 2 . Tunable nontrivial energy gaps ranging from 4 to 238 meV are obtained, guaranteeing further room-temperature observations and applications. The combined effect of strain and electrostatic interaction that can be engineered by the cladding layers leads to a band inversion, resulting in the phase transition from trivial insulator to 2D TCIs. Our work provides a new strategy for engineering topological states in 2D materials.